The crucial role of gadolinium-enhanced MRI in a case of amaurosis fugax - a case report and literature review - Manea Maria Mirabela; Dragoş Dorin; Dobri Ana-Maria; Ghenu Maria Iuliana; Stoican Iulia-Cosmina; Enache Iulia-Ioana; Tuta Sorin (Sciendo, 2024)
Optic perineuritis is the inflammation of the optic nerve sheath. This affliction can lead to visual field impairment and other signs and symptoms related to the orbital space, such as pain, disc edema, ophthalmoplegia, proptosis. However, not all patients present with such suggestive symptoms, requiring a thorough assessment. We report the case of a young male admitted to our hospital for recurrent episodes of monocular blindness. Amaurosis fugax is a well-known presentation of transient ischemic attacks (TIA) and it was ruled out. Gadolinium-enhanced MRI revealed a typical aspect of optic perineuritis. It was mandatory to consider all possible causes of secondary optic perineuritis as they all represent serious clinical conditions, even if the idiopathic form is more frequent. The clinical and paraclinical evaluation of the patient excluded an underlying disease and primary optic perineuritis was diagnosed. Corticosteroid therapy is usually curative and a course of methylprednisolone was initiated for our patient with good outcome. However, response to treatment is not diagnostic as both primary and secondary optic perineuritis are normally responsive, hence thorough differential diagnosis is necessary.